1986
DOI: 10.1128/aem.51.6.1230-1234.1986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of External pH and Fermentation Products on Clostridium acetobutylicum Intracellular pH and Cellular Distribution of Fermentation Products

Abstract: Clostridium acetobutylicum ATCC 824 cells harvested from a phosphate-limited chemostat culture maintained at pH 4.5 had intracellular concentrations of acetate, butyrate, and butanol which were 13-, 7-, and 1.3-fold higher, respectively, than the corresponding extracellular concentrations. Cells from a culture grown at pH 6.5 had intracellular concentrations of acetate and butyrate which were only 2.2-fold higher than the respective external concentrations. The highest intracellular concentrations of these aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 13 publications
(26 reference statements)
0
31
0
2
Order By: Relevance
“…Thus, a reduction of the extracellular pH by only 0.3 units, which would, in turn, cause a reduction of the intracellular pH from 5.4 to 5.1, may have caused the inhibition of solventogenesis. Butanol has been shown to decrease the ApH in C. acetobutylicum (3,6,11,21). Decanol may cause the same effect because linear alcohols often have similar effects, differing only in potency, in biological systems (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reduction of the extracellular pH by only 0.3 units, which would, in turn, cause a reduction of the intracellular pH from 5.4 to 5.1, may have caused the inhibition of solventogenesis. Butanol has been shown to decrease the ApH in C. acetobutylicum (3,6,11,21). Decanol may cause the same effect because linear alcohols often have similar effects, differing only in potency, in biological systems (12).…”
Section: Discussionmentioning
confidence: 99%
“…The build up of acidic products, particularly acetic acid, eventually inhibits further growth of anaerobic cultures, probably by acting as a weak uncoupler [92]. At pH 4.5 the level of acetate inside the cell is several times its external concentration, at least in Clostridia [93]. These observations have been used as the basis for a selection procedure which kills acid-excreting cells [94].…”
Section: Ch3co-scoa + Pi ~ Ch3co-p + Coashmentioning
confidence: 99%
“…The compounds highlighted in bold are those that are antibacterial. As can be observed from (Hamak, 2015;Huang, Forsberg, & Gibbins, 1986;Jain, Ravichandran, Sisodiya, & Agrawal, 2010;Lu et al, 2012;Ramachandran, Rani, Senthan, Jeong, & Kabilan, 2011;Seanego & Ndip, 2012;Sikkema, de Bont, & Poolman, 1995;Vijesh, Isloor, Telkar, Peethambar, & Rai, 2011). It was observed that, the decanoic fractions were highest in case of Soy BA (Figure 7c), followed by Soy A, which was the exact sequence of antibacterial activity observed.…”
Section: Gc-ms Analysis Of Extracts For Antimicrobial Compoundsmentioning
confidence: 65%